Analysis of Factors Influencing Online Purchasing Decisions for Fashion Products on Shopee - Mita Hadi Wijayanti; Ayu Nurafni Octavia (Universal Business and Management Review, 2025)
This study aims to analyze the factors that influence online purchasing decisions for fashion products on Shopee, a case study among the people of Semarang City. The factors examined in this study are price, product reviews, and promotions. The population of this study was the people of Semarang City who had purchased fashion products on Shopee. The sampling technique used purposive sampling, a sampling technique with certain criteria. The criteria used were people of Semarang City aged 17 years and over who had purchased fashion products on the Shopee marketplace. The determination of the number of samples refers to the Cochran formula of 97 respondents. The data collection method used a questionnaire, and data analysis used SPSS which included validity tests, reliability tests, classical assumption tests, multiple linear regression, and hypothesis tests. The results of this study indicate that the variables of price, product reviews, and promotions influence purchasing decisions. The better the consumer's perception of the price offered, the higher the purchasing decision, the better the product reviews, the higher the purchasing decision, and the higher the promotion, the higher the purchasing decision.